SHORTCUT TO TERRORISM: SELF-RADICALIZATION AND LONE- WOLF TERROR ACTS: A CASE STUDY OF INDONESIA - Riyanta, Stanislaus (Journal of Terrorism Studies, 2022)
A surprising phenomenon was observed in the lone-wolf terror terrorism that occurred in Indonesia. This is associated with the fact that the perpetrators of seven out of thirteen cases reported were exposed to radical information through social media and the internet without directly joining a terrorist group. The process involved the intensive exploration of the internet by people previously interested in radicalism content which eventually led to self-radicalization and the subsequent terror acts. Meanwhile, Fathali M Moghaddam proposed that the process of radicalization before a terror act is conducted involves six stages of action known as the staircase to terrorism. This concept was, however, observed to be irrelevant to the lone-wolf terror act considering the fact that the second to fifth stairs are usually reached through a shortcut based on the activities conducted on the internet. Therefore, this study proposed an adjustment to the Moghaddam's staircase to terrorism due to the rise of self-radicalization through the internet and also developed a prevention mechanism which involves community engagement to build community resilience towards preventing the shortcut through the provision of efforts to complement the actions of security forces in order to stem the prevalence of lone-wolf terror in the country.